Formative Assessment: English Teachers’ Perspectives and Practices - Bhim Lal Bhandari (Universitas Islam Malang, 2020)
The study explores English language teachers’ perspectives and practices of formative assessment. In order to achieve the objective, the qualitative research design was used. I adopted the interpretive research paradigm and the qualitative phenomenological research method to bring the lived experiences of the participants. Four teachers from two campuses of Rupandehi were purposively selected as the research participants. The semi-structured interview and open-ended questions were used in order to draw out information from them. The study was carried out within the theoretical framework of constructivism theory. This study reveals English teachers’ good perspectives and practices of formative assessment as they are aware of the value, purposes, and various types of formative assessment. Since their perspective is clear, they use it to improve student's weaknesses, modify their existing practices, and bring desirable changes in time. However, in practice, teachers do not implement all forms of formative assessment to engage students due to their inadequate practical knowledge, time constraints, and large classrooms.